Surface‐modified nanosilica–chitinase (SiNp‐Chs)‐doped nano enzyme conjugate and its synergistic pesticidal activity with plant extracts against armyworm Spodoptera litura (Fab.) (Lepidoptera: Noctuidae). Issue 1 (19th February 2021) - Narendrakumar, G.; Karthick Raja Namasivayam, S.
Abstract: A laboratory experiment was conducted to evaluate enhanced pesticidal activity of silica nanoparticles‐doped chitinase nano enzyme conjugate against an economically important insect pest Spodoptera litura (Fab.) (Lepidoptera; Noctuidae). Silica nanoparticles were synthesized by hydrolysis and condensation of precursor tetraethylorthosilicate (TEOS) followed by functionalization with functioning agent 3‐aminopropyltriethoxysilane. Functionalized silica nanoparticles thus acquired were doped with chitinase enzyme produced by Serratia marcescens SU05. Doped nanosilica–chitinase nano enzyme conjugate was loaded with pesticidal plant extracts to study the improved pesticidal activity. Synthesized nano enzyme conjugate revealed high stable, monodisperse spherical nanoparticles and exhibited effective loading with respective plant extracts. Nano enzyme conjugates and plant extracts loaded with nano enzyme conjugate recorded high rate of mortality against the larval instars and brought about a distinct effect on the life stage parameters of S.litura . Non‐target toxic effect of nano enzyme conjugate was carried out by determination of lethality and changes in protein profiling against brine shrimp ( Artemia salina ) that shows less lethality and no distinct changes in protein profiling which suggest the effective utilization of silica nanoparticles doped chitinase as an insecticidal agent against economically important insect pests associated with various crops.